Implementasi Kebijakan Pengembangan Koleksi Perpustakaan Perguruan Tinggi (Tinjauan Literature Review) - Nihayati Nihayati (Pustakaloka, 2021)
Collection development activities require a collection development policy. Without a collection development policy, like a business without a business plan. This study aims to see the implementation of collection development policies in college libraries. This research is a qualitative study with a literature review. The criteria are articles according to journal research objectives regarding collection development, displayed in full text and publication for the last 5 years. The search for articles was carried out on the Indonesia One Search (IOS) database via https://onesearch.id/ , then the articles were checked according to the criteria. The examination process resulted in 5 articles. Data analysis with data extraction, analyzing data based on the author's name, title, objectives, research methods and grouping important data in articles.The results showed that the implementation of collection development encountered obstacles, including relevance, multiple information or overpublishing, bibliographic supervision, budget and gaps between selection, lack of communication, user analysis, absence of written policies, lack of role of authorized parties to select and lack of tools. help selection, and less trust in librarian. Libraries have not fully held full autonomy in library management, so the contextualization of collection development policies does not run optimally. Another finding is that user involvement in the formulation of collection development policies is very small.